A Comparative Study of Cross-Border and Domestic Acquisition Performances in the South Korean M&A Market: Testing the Two Competing Theories of Culture - Sung-Jun Lee (Sustainability, 2019)
To gain a sustainable competitive advantage through cross-border mergers and acquisitions (M&As), acquiring firms need to correctly anticipate the consequences of national cultural differences. By comparing the cultural antecedents as well as the performances of domestic M&As (DMA) and cross-border M&As (CMA) in the Korean M&A market from 1999 to 2007, this study aims to gauge whether CMAs can be a viable option for a sustainable growth strategy. This paper tests two conflicting hypotheses (H) regarding the effects of cultural differences. From the perspective of the essentialist (“classic„) concept of culture, DMAs will outperform CMAs (H1) because culture clashes may take place less often in DMAs than in CMAs. However, from the perspective of the social constructivist concept of culture, the post-merger performance will be dependent upon the stability and legitimacy of the intergroup status relations between the acquiring and acquired firms regardless of whether it is DMA or CMA (H2). This study also scrutinizes the moderating effects of the level of integration on these two hypothesized relationships (H3 and H4). The results of this paper demonstrate that the social constructivist concept of culture overall provides a better theoretical explanation.